Long-range magnetic ordering in Na2IrO3 - Singh, Yogesh (American Physical Society, 2011)
We report a combined experimental and theoretical investigation of the magnetic structure of the honeycomb-lattice magnet Na2IrO3, a candidate for a realization of a gapless spin liquid. Using resonant x-ray magnetic scattering at the Ir L3 edge, we find three-dimensional long-range antiferromagnetic order below TN=13.3 K. From the azimuthal dependence of the magnetic Bragg peak, the ordered moment is determined to be predominantly along the a axis. Combining the experimental data with first-principles calculations, we propose that the most likely spin structure is a zig-zag structure.
Only IISERM authors are available in the record.